Synthesis, electrochemical, in situ spectroelectrochemical and in situ electrocolorimetric characterization of new phthalocyanines peripherally fused to four flexible crown ether moieties - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Novel Ni(II), Zn(II), Co(II) and Cu(II) phthalocyanines with four peripheral 4-[methyleneoxy(18-crown-6)] groups have been synthesized via the cyclic tetramerization of 4-[{(18-crown-6)-yl}methyleneoxy]phthalonitrile and the corresponding metal salts (NiCl2, Zn(CH3COO)(2), CoCl2 and CuCl2). The thermal stabilities of the metal-free and metallophthalocyanine compounds were determined by thermogravimetric analysis. The structures of the target compounds were confirmed using elemental analysis, IR, H-1-NMR, C-13-NMR, UV-Vis and MS spectral data. Voltammetric and in situ spectroelectrochemical measurements show that while the cobalt phthalocyanine complex gives both metal-based and ring-based redox processes, the metal-free, nickel, zinc and copper phthalocyanines show only ring-based reduction and oxidation processes. An in situ electrocolorimetric method has been applied to investigate the color of the electro-generated anionic and cationic forms of the complexes. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Crown ether; Metallophthalocyanine; Synthesis; Cyclic voltammetry; Spectroelectrochemistry; Chromaticity diagram; METAL-FREE; SOLUBLE METALLOPHTHALOCYANINES; SUBSTITUTED COBALT; PHOTOSENSITIZERS; NICKEL(II); COMPLEXES; ZN(II); SERIES; BIS